IFPA award in placentology lecture: Phylogenomic origins and evolution of the mammalian placenta. (December 2016) - Wildman, Derek E.
Abstract: The placenta has had the most dynamic evolutionary history of all mammalian organs. It has undergone massive shifts in anatomy, physiology, and the way in which uterine and fetal tissue interact with one another during pregnancy. The human placenta is arguably the best studied amongst mammals, yet much about its function during pregnancy is not understood. The purpose of this paper is to outline the evolutionary history of the placenta, and to point out major gaps in the current state of knowledge. I also propose novel theoretical, experimental, and computational approaches that are likely to provide insight into the normal process of placentation and the role the placenta plays in the great obstetrical syndromes.